Aqueous Drop‐on‐Drop Impact on Super‐Repellent Surface. Issue 1 (25th November 2021) - Han, Xing; Tang, Xin; Zhao, Haibo; Li, Jiaqian; Li, Wei; Wang, Liqiu
Abstract: Antiliquid‐accumulation on the surface is desired in practical applications. Super‐repellency of the surface reduces the interaction between impacting drop and the surface effectively. However, for horizontal super‐repellent surfaces, super‐repellency is not enough for liquid removal when drops keep coalescing and remain on the surface. The interaction between impacting drop and static drop can further be beneficial for antiliquid‐accumulation on the surface. Here, aqueous drop‐on‐drop impact on the super‐repellent surface is studied. Weber number of impacting drop and offset distance between drops control impacting outcomes (coalescence or bouncing), while the viscosity of drops influences fluid dynamics after the coalescence. The efficiency of released excess surface energy transferred into mechanical energy during coalescence can be 18.9% for upcoalescence, which is much higher than the efficiency for downcoalescence or in‐plane coalescence (≈6%) as reported in the literature. The bouncing between drops can reduce liquid accumulation on a super‐repellent wafer remarkably (99.1 vol% reduction of accumulated liquid), being a promising method for liquid removal. Abstract : Antiliquid‐accumulation on the surface is desired in practical applications. The interaction between impacting drop and static drop can be beneficial for antiliquid‐accumulation on the surface. Weber number of impacting drop and offset distance between drops control impacting outcomes (coalescence or bouncing), while the viscosity of drops influences fluid dynamics after the coalescence.